The evolution of pertactin expression in Belgian circulating B. pertussis strains, pre- and post-COVID-19 - Martini, Helena; Soetens, Oriane; Niinikoski, Vili; Barkoff, Alex-Mikael; He, Qiushui; Piérard, Denis; Van Honacker, Eveline (American Society for Microbiology, 2026)
Prior to the COVID-19 pandemic, Bordetella pertussis strains not producing pertactin were globally increasing, especially in countries using the acellular pertussis vaccine. Subsequently, during the pandemic, global pertussis incidence dropped to extreme lows, likely due to non-pharmaceutical interventions (e.g., social distancing and face masks). During 2022–2024, many countries—including Belgium—saw a re-emergence of the disease. The newly circulating strains are mostly pertactin-expressing. Pertactin (Prn) antigen-expression testing was performed on 432 Belgian isolates collected in 2014–2023. Whole-genome sequencing for virulence typing and phylogenetic analysis was performed on 416 isolates. Before COVID-19, Prn-negative strains in Belgium went from making up less than 20% of circulating strains to being in the majority from 2017 to 2020. In 2022 and 2023, during the post-COVID re-emergence, all tested strains expressed pertactin. Further typing showed a variety of different mutations of the prn gene and/or its promoter region in the pre-pandemic Prn-negative strains. In phylogenetic analysis, these do not cluster together. Prn-positive B. pertussis strains have replaced Prn-negative ones in Belgium since the post-COVID-19 re-emergence. This could potentially be an effect of reduced population immunity, allowing some strains to spread rapidly with less selective pressure for pertactin deficiency. Further research and surveillance should be done to identify or refute other potential factors influencing pertactin expression.